Disturbed Cholesterol Traffic but Normal Proteolytic Function in LAMP-1/LAMP-2 Double-deficient Fibroblasts - Eskelinen, Eeva-Liisa (The American Society for Cell Biology, 2004)
Mice double deficient in LAMP-1 and -2 were generated. The embryos died between embryonic days 14.5 and 16.5. An accumulation of autophagic vacuoles was detected in many tissues including endothelial cells and Schwann cells. Fibroblast cell lines derived from the double-deficient embryos accumulated autophagic vacuoles and the autophagy protein LC3II after amino acid starvation. Lysosomal vesicles were larger and more peripherally distributed and showed a lower specific density in Percoll gradients in double deficient when compared with control cells. Lysosomal enzyme activities, cathepsin D processing and mannose-6-phosphate receptor expression levels were not affected by the deficiency of both LAMPs. Surprisingly, LAMP-1 and -2 deficiencies did not affect long-lived protein degradation rates, including proteolysis due to chaperone-mediated autophagy. The LAMP-1/2 double-deficient cells and, to a lesser extent, LAMP-2 single-deficient cells showed an accumulation of unesterified cholesterol in endo/lysosomal, rab7, and NPC1 positive compartments as well as reduced amounts of lipid droplets. The cholesterol accumulation in LAMP-1/2 double-deficient cells could be rescued by overexpression of murine LAMP-2a, but not by LAMP-1, highlighting the more prominent role of LAMP-2. Taken together these findings indicate partially overlapping functions for LAMP-1 and -2 in lysosome biogenesis, autophagy, and cholesterol homeostasis.